NCAF - Nagoya Contemporary Art Fair 1992. (Nagoya : Nagoya Contemporary Art Fair, 1992)
Nomura, Hitoshi ; Yoshinaga, Yutaka ; Seko, Tomiyasu ; Schwab, Norman ; Hodgkin, Howard ; Opie, Julian ; Yasuda, Naoka ; Freud, Lucian ; Uchida, Shiro ; Kanemitsu, Matsumi ; Nagasawa, Chimei ; etc.
NCAF - Nagoya Contemporary Art Fair 1992, Nagoya City Gallery, Nogoya, 15 - 26 April 1992
boek